EKSISTENSI MUROBBI ASRAMA DALAM MEREALISASIKAN TANGGUNG JAWAB SANTRI TERHADAP TATA TERTIB PONDOK PESANTREN AS SHOGIR CIAMIS - Luthfi, Rifyal (Program Pascasarjana Institut Agama Islam Tasikmalaya, 2025)
Islamic boarding school is an Islamic educational institution known as a dormitory where students live. Students who live or live in Islamic boarding schools have the responsibility to maintain the good name of the educational institution by complying with all the rules and regulations set by the Boarding School Management. Students who violate the rules will be subject to sanctions or punishment according to the violation they have committed. The decision letter regarding the implementation of the law is based on the results of consideration and approval from various parties who occupy important positions in Islamic boarding schools. Notification regarding Islamic boarding school rules and regulations is delivered in writing attached to the Islamic boarding school registration form so that it indirectly requires students to be ready to carry out their duties and obligations while staying at the Islamic boarding school. Judging from the problems that have been described, the purpose of writing this article is firstly to find out how Murobbi Dormitory realizes the responsibility of students towards Islamic boarding school rules and secondly, how Murobbi Asrama responds to students who violate Islamic boarding school rules. In the author's opinion, Murobbi Asrama, who is the leader of the hostel, will be able to direct the students towards their educational goals. This can be achieved if it is based on desires and intentions as well as self-awareness as a student who bears responsibility for his education at the Islamic boarding school. The attitude of a Murobbi who is patient, authoritative and wise in realizing his role as a leader and educator will require students to have a sense of responsibility for the rules and regulations of the Islamic boarding school